Foreign Exchange Reserves: Component-Wise Analysis - Vanlalramsanga, C.; Golait, Ramesh (Indian Journal of Finance, 2012)
The impressive pace of foreign reserve growth has become an important issue on the international policy agenda and has been considered from various perspectives, including the sustainability of reserve accumulation. Countries holding foreign reserves are projected to be able to better coordinate trade policy and to provide safety nets to the domestic economy from external socks, but with costs. World foreign exchange reserves grew from USD 1.2 trillion in January 1995 to more than 9.6 USD trillion in December 2010. In emerging-market economies alone, reserves increased many-fold during the past decade, and at present, are estimated at over US5 trillion. Countries with adequate reserves generally avoided large drops in output and consumption, and were able to handle outflows of capital relatively better without experiencing significant heat of the crisis. However, holding reserves also entails costs, both directly for the reserve holding individual country, and globally in the form of macroeconomic imbalances. The US dollar is enjoying the privilege of dominating the currency composition of official foreign exchange reserves for a long time, but the dominance is turning slowly away. It is found that an increase in India’s foreign exchange reserve is driven mainly by the foreign-currency assets’ component, while the corresponding increase in the gold reserve component did not occur for a fairly long time. Furthermore, the gold holdings in India, in terms of percentage, are relatively lower compared with increasingly sizable holdings in most of the advanced countries and even some EMEs. In general for all countries, percentage of gold holdings is seen to have been showing an increase.